Hubungan kadar hemoglobin ibu trimester ketiga dengan risiko kelahiran prematur: Literatur review - Lausiri, Satharia; Dewi, Anna Sari; Emilda, Andi (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Anemia in pregnancy is one of the most common maternal health problems globally and often occurs in the third trimester when maternal and fetal physiological needs increase. Low hemoglobin levels have the potential to cause placental hypoxia and increase the risk of obstetric complications, including preterm birth. Purpose: To determine the association between maternal hemoglobin levels in the third trimester and the risk of preterm birth based on the latest scientific evidence from national and international journals. Method: A systematic literature review was conducted based on the PRISMA 2020 guidelines. Twenty-two articles met the inclusion criteria, which included a population of pregnant women in the third trimester, observational study designs or meta-analyses, and reports of preterm birth outcomes. Results: The majority of the 22 articles showed a significant association between low hemoglobin levels (Hb <11 g/dL) and an increased risk of preterm birth and adverse neonatal outcomes such as low birth weight (LBW) and high-birth-weight (SGA). Conclusion: Low hemoglobin levels in the third trimester are significantly associated with the risk of preterm birth. Routine Hb testing prior to delivery and adequate anemia management are needed as strategies to prevent obstetric complications and improve maternal-infant safety. Keywords: Hemoglobin; Pregnancy Anemia; Premature Birth; Perinatal Outcome; Third Trimester. Pendahuluan: Anemia pada kehamilan merupakan salah satu masalah kesehatan maternal paling umum secara global dan sering terjadi pada trimester ketiga ketika kebutuhan fisiologis ibu dan janin meningkat. Kadar hemoglobin yang rendah berpotensi menyebabkan hipoksia plasenta dan meningkatkan risiko komplikasi obstetri, termasuk kelahiran prematur. Tujuan: Untuk mengetahui hubungan kadar hemoglobin ibu trimester ketiga dengan risiko kelahiran prematur berdasarkan bukti ilmiah terkini dari jurnal nasional dan internasional. Metode: Systematic Literature Review dilakukan berdasarkan pedoman PRISMA 2020. Sebanyak 22 diantaranya memenuhi kriteria inklusi yang meliputi populasi ibu hamil trimester ketiga, desain penelitian observasional, atau meta-analisis, dan laporan hasil kelahiran prematur. Hasil: Mayoritas dari 22 artikel menunjukkan adanya hubungan yang signifikan antara kadar hemoglobin rendah (Hb < 11 g/dL) dan peningkatan risiko kelahiran prematur serta outcome neonatal buruk seperti BBLR dan SGA. Simpulan: Kadar hemoglobin rendah pada trimester ketiga berhubungan signifikan dengan risiko kelahiran prematur. Pemeriksaan Hb rutin menjelang persalinan dan penanganan anemia yang adekuat diperlukan sebagai strategi pencegahan komplikasi obstetri dan peningkatan keselamatan ibu-bayi. Kata Kunci: Anemia Kehamilan; Hemoglobin; Kelahiran Prematur; Outcome Perinatal; Trimester Ketiga.